Evaluation, foresight and participation as new elements for regional innovation policy practice: lessons from the regional innovation strategies (RIS) - Silke Nicole Haarich; Elvira Uyarra (European Regional Science Association (ERSA), 2002)
Science, technology and innovation policies are experiencing numerous developments and changes in their orientation and design, which demand corresponding adaptation of policy evaluation methods and practices. Innovation systems are evolving towards more complex socially distributed structures of knowledge production activities, involving an increasing intertwining between science and technology, greater multidisciplinarity and specialisation in technological knowledge bases and a diversity of knowledge generating organisations. These changes require new forms of intervention, based on adaptability, policy learning and evolution, systemic coordination and the enhancement of firms & innovative capabilities. Moreover, there is a regained interest in sub-national (regional and local) levels of accumulation of innovative capabilities. Indeed, regional innovation policies are becoming more and more important, which in turn represents an important opportunity to be seized specially by less developed regions in narrowing the technology gap with more advanced ones. In addition, new and more sophisticated tools of policy intelligence and planning such as technology foresight are being employed. These new tendencies in innovation policies pose new challenges for the assessment and evaluation of these activities. Along with the actual intents to build new and effective capacities, the institutionalisation of evaluation systems is now a precondition for the implementation of organisational learning within the policy and decision making frameworks. Evaluation is definitely one of the most adequate instruments to foster processes of reflexivity and continuous learning within organisations. Even so, evaluation has to be implemented and executed during the entire process of policy design, implementation and analysis to be useful, which requires the development of new capacities and strengthening the existing ones, in order to institutionalise the evaluation practices and build up a comprehensive `evaluation system. Within this context, the demand for evaluation activities and its stimulation is as important as the promotion of the evaluation supply capacities, i.e. the existence of training and qualification facilities for evaluators, the communication between professionals by means of journals, networks, professional organizations, etc. The new regional innovation policies and the need for new evaluation practices suppose now a great opportunity for, on the one hand, the institutionalisation of evaluation within this new policy field and, on the other, the development of new evaluation methods and techniques, adapted to the particularities of regional innovation policy practices and knowledge based activities. The aim of this paper is to inquire into the adequacy of current evaluation systems and methods to the changes in the objectives and practices for regional innovation policies, supported by EU Structural Funds. The paper begins with a brief account of changes in the objectives and guidelines of European regional innovative actions. This discussion is followed by an assessment of the relevance of traditional evaluation practices for the monitoring of the effectiveness of these policies. This analysis will evidence a series of shortcomings and challenges in policy evaluation and will underline the importance of the institutionalisation of evaluation. This framework will be illustrated using evidence of innovative actions in Spanish regions. Practical policy recommendations will be advanced in the final section.
Keywords: 330